Review of Non-Communicable Disease Research Activity in Kuwait: Where is the Evidence for the Best Practice? - Hanan Badr; Mohamad Ali Maktabi; Manal Al-Kandari; Abla Mehio Sibai (Ubiquity Press, 2019)
Background: Kuwait, a small country in the Middle East, is now facing rapid development, with non-communicable diseases (NCDs) accounting for the majority of deaths. Objectives: In this study, we review trends in NCD research productivity in Kuwait and examine to what extent it is aligned with disease burden. Methods: Systematic mapping of NCD papers produced between January 2000 and December 2013 yielded 893 publications. These were defined according to study design, study focus, and risk factors examined. Research gaps were assessed by examining disparities between literature produced and cause-specific proportional mortality rates (PMR) and disability-adjusted life years (DALYs). Findings: While annual publication rates increased more than two-fold during the study period, many of the study methodologies were descriptive (58%). Only 2.6% were based on high-evidence interventional studies. Cancer, CVD, and diabetes featured in 38.1%, 15.1%, and 9.2% of the publications, respectively. Compared to PMR and DALYs, there was a surplus of cancer research, most of which were laboratory-based studies (27.6%) or of the case-report/case-series study type (26.5%). Smoking was more likely to be addressed in relation to CVD (32.6%) than diabetes (6.1%) or cancer (2.1%). Physical inactivity was mostly examined in its relation to diabetes (14.6%), with negligible representation in the remaining study focus (range 0.3% to 2.2%). Conclusion: NCD research production in Kuwait is not aligned with disease burden or health priorities. We recommend a coordinated action between funding agencies, universities, and researchers in Kuwait to guide development of a comprehensive research agenda that is responsive to the country's emerging needs.